A new species of Nemipterus (Perciformes: Nemipteridae) and first record of N. nematophorus (Bleeker) from Taiwan - Russell, Barry C.; Ho, Hsuan-Ching (Zootaxa, 2017)
A new species of threadfin bream, Nemipterus sugillatus, from Taiwan and Indonesia is described and figured. Nemipterus sugillatus n. sp. resembles N. virgatus (Houttuyn) in colour pattern but differs from the latter, notably in lacking a second yellow stripe along the base of the dorsal fin, and by the absence of a red spot at the origin of the lateral line. Nemipterus sugillatus n. sp. is also distinct from N. virgatus in having only 7 anal soft rays (versus 8) and in lacking a long trailing caudal filament. Nemipterus nematophorus Bleeker is reported for the first time from Taiwan. A key to the species of Nemipterus from Taiwan is provided.